The copywriter's toolkit the complete guide to strategic advertising copy - Berman, Margo, 1947- (Wiley-Blackwell, 2012)
"It doesn't matter whether you're a student, novice, or seasoned professional, this book will hone your copywriting skills. Beginning with strategy and technique, each following chapter focuses on writing for a specific medium: from print and broadcast through ambient and digital media. Writing examples are shown using industry standard formats. You'll quickly see how radio scripts differ from TV scripts, how television storyboards are best presented, and how print copy is typed up to facilitate typesetting. Copywriters from global agencies share their writing secrets and offer copy tips for every medium. Special callout boxes will make major points easy to remember and simple to apply. Glossaries are listed in relevant chapters and checklists summarize the principles for fast reference. Written from a real-world perspective by an award-winning copywriter/producer/director, this comprehensive guide is what every writer needs to create powerful, strategic ad copy"--